Methods of weight loss in training for wrestlers - Liu, Y.; Feng, L. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The aim of this study is to provide a reference for weight loss in wrestlers prior to competition. The factors being observed were load and content of training and time of weight loss. This data was provided through analysis of observed findings and the results of surveys completed by athletes and coaches. Methods Analysis of the training characteristics of 11 wrestlers who participated in the Chinese National games was undertaken. The analysis considered the training load before the competition, as given by training intensity and weekly training load This was broken down into distribution of training content and the time period of the training program. Results High intensity specific mat (special) training was the dominating form of training in the group that slowly reduced body weight. In contrast, middle and low intensity training dominated the fast body weight loss group. The total time used in the mat training during the group that lost weight slowly was longer than the group that reduced body weight rapidly. The time spent training by the slow weight loss group was longer than that used in the rapid weight loss group; and the time spent on special technique training in the rapid weight loss group was the same as the slow weight reduction group. In both groups, there was an obvious decrease in body weight, and the percentage of body fat. Conclusions Training load and planning for competition weight is important in the sport of wrestling where there are weight categories. There is always a question of whether or not rapid weight loss or gradual weight loss will affect the performance of individuals. The findings suggested that while both groups lost weight, it would be better to manage it over time than rapidly. Rapid weight loss may affect performance in the competition.